Efectividad del programa educativo“Ejercicio es Vida”en los conocimientos, actitudes y prácticas sobre el ejercicio físico que poseen los estudiantes del 3° año de enfermería de la Universidad Peruana Unión, abril -junio 2010. - Miranda Limachi, Keila Ester (2019)
Objective: To determine the effectiveness of the educational program “Exercise is life” in knowledge, attitudes andpractices about physical exercise held by the 3rd year students of nursing, Universidad Peruana Unión, April-June2010. Methods: Study pre-experimental type, design pre-test and post-test with one group, longitudinal section. Weused non-probability sampling for the convenience of the researcher, was based on inclusion and exclusion criteriapreviously established, this sample was taken from the 3rd year of Nursing, participation was voluntary, yielding atotal of 22 students. The program was organized in 25 theoretical and practical educational sessions with a frequency of 3 times a week for two months. Results: The obtained results were efective, because before applying to theprogram “Exercise it is life”, 95.5% obtained a level of good knowledge, the 100% had positive attitudes, and the95,4% had a level of deficient and regular practice. After the program, the 100% had a level of knowledge betweenvery good and excellent, 100% held positive attitudes, specific changes were related to items on the Likert scale,before the program highlights the answers “indifferent” and “agree” and after the program, the responses “agree”and “strongly agreement “had the highest percentage and the 100% presented an excellent level of practices inthe aerobic physical exercise. Performing the T test analysis for related samples to 95% reliability, confirming theeffectiveness of the program in the sense that the students have increased their knowledge, attitudes and practicesabout physical exercise, with a value of 0.00. Conclusions: The educative program “Exercise is life” was effectivebecause improved the knowledge, attitudes and practices of the 3° students of º nursing of the Faculty Sciences ofthe Health of the Peruvian University Unión.